Determining quality of technologies taking into account main production and organizational measures - E. M. Zimin; V. V. Martishkin (Омский научный вестник)
The article presents the list of singular indicators of technological support of technologies and the method of determining their actual values and their quality levels. According to the results of determining the quality level of technological processes, one of three management decisions can be made. The paper describes singular quality indicators that are directly related to the quality of technological processes in the machine-building industry, at the stage of design and preparation of technical documentation. And also presented are complex quality indicators, based on which determine the generalized indicator of quality of the evaluated technological process. As a result of the work the features of conformity assessment of technological processes and related mandatory requirements are formed. Also described is the process of obtaining a qualitative and quantitative assessment of the quality of the technological process with a detailed description of all necessary formulas.